BIOMIND Module: A Quality Teaching and Assessment Media - Rian Vebrianto; Alaniyah Syafaren (Journal of Educational Science and Technology (EST), 2018)
Teaching media is one essential factor that influences the success of teaching process. Therefore, this study was aimed to develop a science learning module namely BIOMIND Module in the form of portal and e-book. The study used to research and development (R&D) method to create BIOMIND module developed from Hanafin and Peck model. The study involved five professionals, 20 teachers, and 98 students to assess the BIOMIND module. The results show that BIOMIND portal and e-book teaching media could be standardized and implemented in the teaching process. The existence of teaching media evaluation instrument was expected to develop a quality teaching media for innovative and efficient teaching and learning process.